The Effect Of The Thinking Aloud Pair Problem Solving (TAPPS) Method of Ability Mathematical Communication - Naibaho, Anemsinta; Sinaga, Christa Voni Roulina; Tambunan, Lois Oinike (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the Effect of Thinking Aloud Pair Problem Solving (Tapps) Method on Mathematical Communication Skills of Students of HKBP Private Vocational School Pematangsiantar. The type of research used by the researcher is experimental research. Experimental research is a research to determine whether there is an effect of something imposed on the subject of investigation. This research will be conducted using a single case study design (one-shot case study), where one group of experimental classes becomes the research subject. In the experimental group, a treatment is applied in the form of the application of the Thinking Aloud Pair Problem Solving (TAPPS) Learning Method which is considered successful. After the treatment, a post-test evaluation is carried out and from the results of the measurement, conclusions will be drawn. Based on the results of data analysis and discussion, it can be concluded that there is a significant influence of the Thinking Aloud Pair Problem Solving (TAPPS) Method on students' mathematical communication skills in Statistics material at HKBP Private Vocational School Pematangsiantar. This influence can be seen from the regression equation = -56.532 + 1.088 with a regression coefficient of 1.088 and a determination coefficient of 91% which shows that there is a very strong relationship between the Thinking Aloud Pair Problem Solving (TAPPS) Method and students' mathematical communication skills